Structural Equation Model of Chanthaburi Fruit Market’s Integrated Marketing Communication to Increase Business Capability with China as a Trading Partner - Phuengsamran, Paradee; Sonprajuk, Pnomsit (Business Administration and Management Journal Review, 2023)
The objectives were to develop the structural equation model of Chanthaburi fruit market’s integrated marketing communication to increase business capability with china as a trading partner. This research was quantitative research. Data were collected by 285 GAP-certified farmers in Chanthaburi. The indices measure the Goodness of Fit evaluation criteria. The findings revealed that the research model was consistent with empirical data. The chi-square/df was 2.24, the RMSEA was 0.06, the GFI was 0.90, the CFI was 0.92, and the NFI was 0.90. Results show that 1) the fruit factor has a direct influence on integrated marketing communication. 2) the fruit factor has a direct influence on the increase of business capability, and an indirect influence with integrated marketing communication as a mediator variable. 3) the intercultural competence is found to have a direct influence on integrated marketing communication. 4) the intercultural competence has direct influence on the increase of business capability. Results show that an indirect influence through a mediator variable of integrated marketing communication to the increase of business capability. Finally, 5) the integrated marketing communication has a direct influence on the increase of business capability.